2017
DOI: 10.1016/j.jbusres.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A social commerce investigation of the role of trust in a social networking site on purchase intentions

Abstract: Trust has always been a critical issue in online shopping environments. However, it is even more important in social commerce platforms, due to the salient role of peer-generated contents on users' purchase intentions. This study investigates the relationship between trust of social commerce and users' purchase intentions and proposes a mechanism explaining the relationship. Thus, we present a main and two alternative models by drawing on the critical notions related to purchase intention, including social com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
350
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(431 citation statements)
references
References 86 publications
(131 reference statements)
19
350
0
15
Order By: Relevance
“…We therefore included this expertise as part of our model. Therefore, relationship quality between the vendor (B2B E-commerce platform), is greatly influenced by the vendor characteristics which include: usability of the online platform, level of expertise of vendor in receiving orders and executing them, the behavior of the vendor which touches on his level of trust, his reputation as perceived by the other E-commerce platform and online users and virtual communities (Hajli, Sims, Zadeh, & Richard, 2017).…”
Section: Page174mentioning
confidence: 99%
“…We therefore included this expertise as part of our model. Therefore, relationship quality between the vendor (B2B E-commerce platform), is greatly influenced by the vendor characteristics which include: usability of the online platform, level of expertise of vendor in receiving orders and executing them, the behavior of the vendor which touches on his level of trust, his reputation as perceived by the other E-commerce platform and online users and virtual communities (Hajli, Sims, Zadeh, & Richard, 2017).…”
Section: Page174mentioning
confidence: 99%
“…In recent years, social commerce has emerged as a significant subset of the e-commerce domain (Zhang & Benyoucef, 2016) in which consumers involve the use of social media and user contributions to inform their purchasing activities (Hajli, 2015;Hajli & Sims, 2015). Social commerce is therefore a form of commerce resulting from the combination of commercial and social activities, being underpinned by Web 2.0 technologies in order to facilitate customer interactivity and content generation (Hajli, Sims, Zadeh, & Richard, 2017), and in being mediated by social media (Wang & Zhang, 2012), reintroduces to an extent, some of the social aspects of shopping (Lu et al, 2016). With an estimated 2.46 billion social media users globally, and more than 71% of Internet users having some form of social media account (Statista, 2018b), coupled with the fact that consumers often rely on the advice and recommendations of online friends when making purchase decisions (Chen & Shen, 2015), the commercial potential for social commerce is clear.…”
Section: Introductionmentioning
confidence: 99%
“…Against this backdrop, SNS advertisement has gained a great deal of attention in recent years due to its potential effect on online shoppers' responses (Dehghani et al, 2016). While previous studies have identified the impacts of SNS advertisement on basic consumer reactions such as purchase intention (Hajli et al, 2017), a significant gap remains in the theoretical understanding of how SNS advertisements influences consumer purchase decision (Gilani et al 2019;Nash, 2018;Zhao & Li 2019;Erkan & Evans 2018). This study sets out to fill this gap in the literature by investigating the effects of SNS advertisement on consumers' purchase decision.…”
Section: Introductionmentioning
confidence: 99%